Virtualni 360° ogledi kot orodje promocije kulturne dediščine - Oštrbenk, Katarina (Annales. Series historia et sociologia, 2025)
Virtual 360° tours, digital replicas of real locations accessible anywhere with an internet connection, include 360° panoramic photos and interactive elements such as videos, audio narration, and textual descriptions. Their significance increased during the COVID-19 pandemic, when museums had to temporarily close their doors to visitors. After the pandemic ended, their use as a substitute for visits declined, but the question of their impact on the intention to visit the museum, i.e., for promotional purposes, remains. The paper presents the results of an experimental study conducted in 2023 with 165 residents of the Republic of Serbia regarding their responses to the promotion of the Posavje Museum Brežice. The participants were randomly divided into three groups based on the increasing modality of the medium they were exposed to: photos, a video, and a 360° virtual tour of the Posavje Museum Brežice. The results showed statistically significant differences between all three groups. The 360° virtual tours were rated higher than videos, and videos were rated higher than photos on the media experience variables: enjoyment, sense of presence, autonomy, and satisfaction. The intention to visit was significantly higher with the 360° virtual tour and was statistically significantly associated with the media experience variables. We discuss the results and the future use of virtual 360° tours in heritage promotion.
Keywords: digitalizacija kulturne dediščine; digitisation of cultural heritage; modality; modalnost; Posavje Museum Brežice; Posavski muzej Brežice; promocija kulturne dediščine; promotion of cultural heritage; virtual 360° tours; virtualni 360° ogledi